Exploring process ‘verbs’ in EFL postgraduates’ citations: A Systemic Functional Linguistics approach - Jomaa, Nayef Jomaa; Bidin, Siti Jamilah (Indonesian Journal of Applied Linguistics, 2019)
Due to their significance in establishing a research background, citations have been under focus by several researchers. However, limited studies have applied the Functional Theory in analysing reporting verbs in citations. Hence, this study identifies citations in the literature review chapters of 20 PhD theses in Information Technology and Applied Linguistics by EFL postgraduates within the ESL context. These PhD theses were selected purposefully. This study explores qualitatively the processes based on the ideational metafunction of the Systemic Functional Linguistics. The findings show that the material processes were used dominantly, followed by relational, verbal, and mental processes, whereas the behavioural  processes were less used. The use of processes ‘verbs’ is influenced by field and tenor as register variables. Thus, the findings imply that EFL postgraduates are unaware of using processes; therefore, they should receive discipline-specific instructions. Pedagogical textbooks for academic writing could be also developed based on the outputs of the present study.